Estimating Current and Potential Bicycle Use for Statewide Planning. Issue 1 (2016) - Grover, David; Wygonik, Erica; Bucossi, Sommer; Bell, Amy; Piper, Sam; Brewer-Colie, Katelin
As interest in bicycling for transportation and recreation has increased, state transportation agencies and other planning organizations must prioritize ways in which to spend their limited resources. This paper describes a geographic information system–based analysis that categorizes state-owned highways across Vermont on the basis of potential bicycle use through the leverage of readily available data. This methodology allows a planning agency to make decisions on the basis of statewide information and avoids the costs of a traditional travel demand model. It informs decision makers about where to invest additional funds to improve on-road bicycle facilities and to prioritize maintenance to maximize value. It also provides the groundwork for bicycle-related performance standards and to identify critical gaps in high-demand bicycle corridors.